Analisis Kesesuaian Prinsip Syariah dalam Praktik Utang-Piutang Berbasis Fintech: Studi Kasus Pengguna Aplikasi Akulaku - Abdus Salam (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study critically examines the compliance of fintech-based debt-credit practices, specifically within the Akulaku application, with Islamic Sharia principles. It addresses the rapid growth of online lending in Indonesia and the increasing need for Sharia-compliant financial solutions among the Muslim population. Employing a qualitative descriptive methodology, the research analyzes Akulaku's operational mechanisms, product offerings (Akulaku Paylater, KTA Asetku, Dana Cicil), and terms and conditions against the foundational concepts of qardh (loan) and riba (interest/usury) in Islamic law, drawing upon relevant DSN-MUI fatwas. Findings consistently indicate that while Akulaku offers convenience and quick access to funds, its imposition of additional charges on principal loans and late payment penalties constitutes riba qardh and riba jahiliyah, rendering these practices non-compliant with Sharia principles, particularly DSN-MUI Fatwa No. 117/II/2018. The study highlights the negative implications for users, who often face burdensome repayments and psychological stress. It concludes that despite its modern facade, Akulaku's current debt-credit model requires significant reform to align with Islamic economic principles, offering crucial insights for users, developers, and regulators in the burgeoning Islamic fintech sector.